The Role and Responsibility of Pesantren in Facing Moral Degradation - Badrudin, Badrudin (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
Pesantren is an original Indonesian education based on Islamic values and a moral fortress. Pesantren is a base to protect people from various kinds of moral damage that impact the quality of the nation's future. This study aims to describe the role and responsibility of Pesantren in facing moral degradation in Pesantren Al-Hadi Ciruas Serang Banten. This qualitative case study research was conducted over two months using data collection techniques through interviews, observation, and documentation. Data analysis used triangulation techniques. Data analysis collects, reduces, presents, and verifies data. This study found that the Al-Hadi Islamic Boarding School implements character education by practicing the values that form the character of a modern Islamic boarding school and then implementing it in the learning process, forming Islamic boarding school culture, co-curricular activities, and extracurricular activities. Integrally the whole process of education and learning in Islamic boarding schools forms a distinctive culture of Islamic boarding schools that distinguishes it from the education system outside Islamic boarding schools. The values developed are (1) sincerity; (2) simplicity; (3) independence; (4) brotherhood based on religious spirit and care for the environment. The values that shape the character of modern Islamic boarding schools are then implemented in the learning process, the formation of Islamic boarding schools culture, and co-curricular and extracurricular activities. The values developed are (1) sincerity; (2) simplicity; (3) independence; (4) brotherhood based on religious spirit and care for the environment.